Mode of action of the peptide antibiotic nisin and influence on the membrane potential of whole cells and on cytoplasmic and artificial membrane vesicles. - Ruhr, E (1985)
The peptide antibiotic nisin was shown to cause a rapid efflux of amino acids and Rb+ from the cytoplasm of gram-positive bacteria (Staphylococcus cohnii 22, Bacillus subtilis W 23, Micrococcus luteus ATCC 4698, and Streptococcus zymogenes 24). It strongly decreased the membrane potential of cells as judged by the distribution of the lipophilic tetraphenylphosphonium cation. Ascorbate-phenazine methosulfate-driven transport of L-proline by cytoplasmic membrane vesicles was blocked after addition of nisin, and accumulated amino acids were released from the vesicles. Soybean phospholipid (asolectin) vesicles were not affected by nisin. The data suggest that the cytoplasmic membrane is the primary target and that membrane disruption accounts for the bactericidal action of nisin.